2014
DOI: 10.1270/jsbbs.64.362
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci associated with boiled seed hardness in soybean

Abstract: Boiled seed hardness is an important factor in the processing of soybean food products such as nimame and natto. Little information is available on the genetic basis for boiled seed hardness, despite the wide variation in this trait. DNA markers linked to the gene controlling this trait should be useful in soybean breeding programs because of the difficulty of its evaluation. In this report, quantitative trait locus (QTL) analysis was performed to reveal the genetic factors associated with boiled seed hardness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…For example, cultivated soybeans show different degrees of seed coat permeability that are controlled by quantitative trait loci (17,18). Recently, a quantitative trait locus encoding calcineurin-like protein, GmHs1-1, was isolated by map-based cloning and reported to contribute to hardseededness in soybean with unknown mechanism (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cultivated soybeans show different degrees of seed coat permeability that are controlled by quantitative trait loci (17,18). Recently, a quantitative trait locus encoding calcineurin-like protein, GmHs1-1, was isolated by map-based cloning and reported to contribute to hardseededness in soybean with unknown mechanism (20).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical composition analysis revealed that the impermeable seeds contained a higher amount of hydroxylated fatty acids than permeable seeds (14). At the molecular level, seed hardness has been identified as a quantitative trait in soybean (17,18). With quantitative trait locus marker analysis, two single nucleotide polymorphism alleles were found to be associated with a seed coat permeability trait in various soybean cultivars (19,20).…”
mentioning
confidence: 99%
“…Soybeans were planted and grown in the experimental field at NARO Institute of Crop Science (NICS), Ibaraki, Japan, in 2013 according to the method previously described. 7 The sowing date of Natto-shoryu, Hyoukei-kuro 3, and their progenies was June 25, and that of other cultivars was June 18. Soybean cultivars grown in different locations in 2013 were collected from Kumamoto (Southern area of Japan) and Akita (Northern region of Japan) prefectures as described in Table 1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…An RIL population derived from a cross between two Japanese cultivars, Natto-shoryu and Hyoukei-kuro 3, was prepared according to a previously described method. 7 To survey the candidate genetic region and validate the effect of a major QTL (qHbs3-1), we selected a heterozygous plant of the fifth filial generation (F 5 ) from the RIL population using DNA markers in the region proximal to the QTL. The residual heterozygous line (RHL) 16 in the F 5 generation was self-fertilized, and the resultant F 6 plants were harvested individually in 2011.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation